Trends Financial Technology Usage Decision for Resilience in Urban Society: Impact of New Normal Era Covid-19 - Sylvia Samuel; John Tampil Purba; Sidik Budiono (Jurnal Keuangan dan Perbankan, 2022)
The main objective of the research was to discuss the influence of financial technology on usage decisions for resilience and how the systems give services to accommodate the needs of the consumers. The pilot study was guided by specific aims and goals to evaluate the number of online platforms in Indonesia that can impact millennial generations' usage decisions in urban society. Furthermore, questionnaires were collected based on the purposive sampling technique in the Indonesian market. 400 respondents participated in an online survey, and only 349 respondents that provided valid results can be selected to participate in this study. The findings of this study indicate that advertisement positively relates to usage decisions of fintech. In addition, electronic word of mouth and electronic service quality showed a positive relationship to usage decisions of fintech. Lastly, the brand image shows an insignificant effect on the purchase decision of fintech. Finally, the study results that online platform gives strengthen potential strategies in financial technology by using advertisement, electronic service quality, and electronic word of mouth in sustainability and growth.